Efeito da qualidade do habitat sobre o estado nutricional de pequenos mamíferos não-voadores no Cerrado - Rodrigues, Dine Romero (2021)
The loss, fragmentation and degradation of native vegetation areas by human activities have been the main cause of species loss. Understanding how species respond to the impacts of these processes is crucial in a conservation approach, especially as species respond differently to environmental changes. These changes have the potential to affect the physiological processes and nutritional conditions of individuals and, consequently, their fitness. The nutritional status of an individual can be assessed by body condition indices, which allow estimating their energy reserves, which, in turn, are correlated with ecological parameters such as reproduction, mortality, vulnerability to disease and predation. Within this context, I investigated the effects of habitat loss, habitat quality, climatic season and sex on body condition (calculated by the scaled mass index) of two species of small arboreal mammals in fragments of semideciduous forest in the Cerrado (Gracilinanus agilis and Rhipidomys sp.). It was expected that the loss and reduction of habitat quality would negatively affect the body condition of the species and that this effect would vary with the climatic season and with the sex of the individuals. However, habitat loss did not affect the body condition of the species, while quality had a negative effect on the body condition of Rhipidomys sp. when considering the habitat structure, but without the effect of primary productivity (estimated by the normalized difference vegetation index - NDVI). On the other hand, G. agilis had its body condition negatively related to the temporal variation of the NDVI, but it varied independently of environmental changes. The climatic season had no influence on the body condition of the species and sex only had an effect on the condition of G. agilis, with males showing better body condition than females. The body condition of Rhipidomys sp. was higher in the smaller and disturbed fragments, that can present greater abundance of resources such as fruits and arthropods because they are in the initial stages of regeneration. On the other hand, the body condition of G. agilis seems to be determined by its growth pattern and by the absence of generational overlap, which occurs due to its semelparity. Therefore, responses to environmental changes are species-specific, which makes it important to consider studies with species with different functional attributes and carry out long-term monitoring, in addition to including other health and individual performance parameters to assess the persistence capacity of species in forest fragments in the Cerrado.